Efektivitas Regulasi Penegakan Hukum terhadap Pelaku Illegal Logging di Kuningan - Cahyaningsih, Wulan; Andriyani, Yani; Fathanudien, Anthon; Akmaddhian, Suwari (Universitas Kuningan, 2024)
Forests have a very strategic role in human life, the forestry sector has also been able to help in encouraging national economic growth. Even though it has such a big role and benefits for life, in its management there are still irregularities in forests that damage the forest ecosystem. One form of forest destruction is illegal logging, which currently still frequently occurs, including in Kuningan Regency. The existence of illegal logging acts raises questions about the effectiveness of existing law enforcement regulations for illegal logging crimes based on the current regulations. The aim of this research is to determine and analyze the regulation and effectiveness of law enforcement against illegal logging perpetrators in Kuningan Regency. The research method uses descriptive analytical research specifications with an empirical juridical approach method, research stages using literature study and field research, data collection techniques using primary, secondary and tertiary data, as well as data collection tools using observation and interviews, qualitative data analysis. The results of the research show that regulations regarding the criminal act of illegal logging are regulated in Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction, in law enforcement referring to the Criminal Procedure Code (KUHAP), and Regulation of the Head of the National Police of the Republic of Indonesia Number 6 of 2019 concerning Criminal Investigation. Law enforcement against perpetrators of illegal logging crimes based on Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction is influenced by several factors such as legal structure, legal substance and community legal culture. The conclusion of this research is that regulations regarding illegal logging have been regulated in Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction, with the articles that are often charged with perpetrators being Article 82 and Article 83 of that law. It is recommended that there be collaboration between law enforcers in Kuningan Regency to conduct outreach to the community regarding the impacts of illegal logging, both on the environment and on the perpetrators.